Fish sanctuary establishment and management at Culasi, Antique descriptions, processes, problems and benefits - Angor, Lorna H. (University of the Philippines in the Visayas, 2001)
This study was conducted to describe the establishment and management of fish sanctuaries in Culasi, Antique, to identify problems and benefits as well as to come up with solutions to these identified problems of the four marine sanctuaries. A semi-structured interview was used and responses were validated with the NGO and GO implementers. esults showed that the processes undertaken prior to the establishment of fish sanctuaries were; seminars and trainings, ducational trip, site identification, site survey, management plan formulation, barangay ordinance formulation,public hearing at the barangay, submission of formulated barangay ordinance to the SB, public hearing on municipal level, evaluation of the SB on the ordinance and SB approval. Results wer validated in a focused group discussion. Findings show that fish sanctuaries have improved reef condition and stopped illegal fishing activities which helped increase fish catch and increase income of fishermen. However, such benefits should be sustained by giving solutions to problems that crop up such as lack of monitoring equipment and facilities, lack of alternative livelihood, no zoning plan, deficient organizational structure, lack of financial support and no participatory management.